Construction of a Bi2MoO6/CoOx/Au system with a dual-channel charge transfer path for enhanced tetracycline degradation. Issue 18 (16th August 2022) - Han, Tongyu; Chen, Yigang; Shi, Haifeng
Abstract : The introduction of two cocatalysts CoO x and Au constructs dual carrier transfer channels, which improves the photogenerated electron–hole pairs separation efficiency and photocatalytic performance. Abstract : In the development of environment-friendly photocatalytic technology, improving the separation efficiency of photogenerated electron–hole pairs is an arduous challenge. Herein, different types of cocatalysts Au and CoO x were successfully loaded on the surface of Bi2 MoO6 (BMO) nanosheets through the photodeposition method. The ternary BMO/CoO x /1.5Au composite displayed an enhanced degradation rate of tetracycline (TC), which was 2.75 times higher than that of pure BMO. The significantly improved photocatalytic performance could be attributed to the synergistic effect of the two cocatalysts. With the assistance of Au and CoO x, the photocatalytic system enhanced the visible light absorption capacity and constructed dual channels to accelerate the transfer of electrons and holes, thus suppressing the recombination of photogenerated carriers. Noticeably, the photocatalyst possessed excellent stability, and could still maintain a high activity after five cycles. Meanwhile, photoluminescence analysis (PL) and time-resolved photoluminescence spectroscopy (TRPL) demonstrated that the system promoted charge transfer and prolonged the lifetime of carriers. This research provides insights into designing practical and efficient photocatalysts to remove organic pollutants and sheds new light on constructing charge transfer dual-channel for boosting charge separation.